Pendidikan Bisnis di Jurusan Administrasi Bisnis dan Sekolah Bisnis - Situmorang, James Rianto (Jurnal Administrasi Bisnis, 2009)
Business education is the enterprise of education at the study and research of the fieldof business, usually in university education. It is oriented toward preparing studentsfor the practice of an occupation in business or business related fields. Businesseducation usually thought in a business school, is a university level institution thatconfers degrees in Business Administration. It teaches topics such as accounting,finance, marketing, human resource management, organizational behavior. In Indonesia,Business Administration is a department or a study program of a faculty suchas Department of Business Adminitration, Faculty of Social and Political Sciences,Parahyangan Catholic University. Business school includes school of business, businessadministration and management. They use combination of theory, case studymethod, simulation and practice.